A method for subject-specific modelling and optimisation of the cushioning properties of insole materials used in diabetic footwear. Issue 6 (June 2015) - Chatzistergos, Panagiotis E.; Naemi, Roozbeh; Chockalingam, Nachiappan
Highlights: We developed a new method for the subject specific modelling of the heel pad. Validation showed it can estimate the pressure reduction achieved by insole materials. Its purpose is to inform insole material selection on a subject-specific basis. Altered plantar tissue stiffness or thickness is not important for insole selection. Subject specific loading is very important for insole material selection. Abstract: This study aims to develop a numerical method that can be used to investigate the cushioning properties of different insole materials on a subject-specific basis. Diabetic footwear and orthotic insoles play an important role for the reduction of plantar pressure in people with diabetes (type-2). Despite that, little information exists about their optimum cushioning properties. A new in-vivo measurement based computational procedure was developed which entails the generation of 2D subject-specific finite element models of the heel pad based on ultrasound indentation. These models are used to inverse engineer the material properties of the heel pad and simulate the contact between plantar soft tissue and a flat insole. After its validation this modelling procedure was utilised to investigate the importance of plantar soft tissue stiffness, thickness and loading for the correct selection of insole material. The results indicated that heel pad stiffness and thickness influence plantar pressure but not the optimum insole properties. On the other hand loading appears to significantly influence the optimum insole material properties. These results indicate that parameters that affect the loading of the plantar soft tissues such as body mass or a person's level of physical activity should be carefully considered during insole material selection.